Curt Sachs Is No Longer Number One! Confronting Chinese Students' Expectations of Essentialist Theorizing in Dance Research. Issue 1 (2nd January 2022) - Rowe, Nicholas; Heyang, Tuomeicerin; Wang, Miao; Xiong, Xi; Liu, Yue
ABSTRACT: Chinese postgraduate dance students can be surprised by epistemological expectations when commencing research degrees outside China. This can result from translations into Mandarin of very dated dance scholarship from Europe. Specifically, Curt Sachs' 1933 book World History of the Dance continues as a pervasive representation of Western dance scholarship in current dance research published in Mandarin. Within this article we collate key examples of academic literature published in Mandarin during the last twenty years to show how World History of the Dance continues to be used to support essentialism in dance research in China. We connect this with critical arguments from international dance scholars, identifying why Sachs' publications from the early 20 th century have been rejected within English language academic journals. While this comparative analysis of dance scholarship reveals deep epistemological differences across learning cultures, this paper further evidences how essentialist theories can construct cultural hierarchies in dance.